Effect of number of posterior occluding pairs of teeth to nutritional status in elderly in Yogyakarta (Berita Kedokteran Masyarakat (BKM), 2019)
Purpose : Decreasing number of posterior occluding pairs (POP) of teeth in elderly can lead them to reduce food intake and impaired nutritional status through food intake mediation. This study was aimed to assess the relationship between POP of teeth and nutritional status through food intake mediation.Method : This study was a cross-sectional study involving 130 elderly subjects. Sampling was done by multistage stratified cluster random sampling method. The number of POP of teeth was calculated using the Eichner Index and ordinally categorized into 9 subgroup of occlusion (A1-C2). Nutritional status was measured using the body mass index (BMI) and food intake was assessed using body weight discrepancy in the last 3 months. Data were analized using test of Somer’s d, chi square and path analysis.Results : Mean age was 65,7 years old. There were only 23% of elderly who had POP of teeth in 4 zones and 3.8% of them still had complete POP of teeth (A1), indicated that the lost of large number of POP of teeth was experienced by 77% of the elderly. There was a significant correlation between number of POP of teeth and nutritional status mediated by food intake. A positive relationship between number of POP of teeth with food intake (p = 0,002; r = 0,095) proved that food intake was a mediator.  Conclusion : There was a relationship between number of POP of teeth and nutritional status mediated by food intake.